A Study of the NGF Gene Intron in the Philippine Scrubfowl (Megapodius cumingii) from Kabetan Island, Central Sulawesi - Wayan Windyawati; I Made Budiarsa; Zulaikhah Dwi Jayanti; Manap Trianto; Abdul Ashari; I Nengah Kundera (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The Philippine scrubfowl (Megapodius cumingii) is a bird species that utilizes environmental heat to incubate its eggs and has a wide geographic distribution across various habitats, including coastal forests, coastal areas, and small islands. This study aimed to describe and analyze the genetic diversity and phylogenetic relationships of Megapodius cumingii based on the Nerve Growth Factor (NGF) gene. Genomic DNA was isolated from blood samples of M. cumingii using the gSYNC™ DNA Extraction Kit (Geneaid) protocol and subsequently amplified using the Polymerase Chain Reaction (PCR) method with the forward primer AllNGF5' and reverse primer AllNGF3'. Sequence data were analyzed using BLAST to determine their similarity to reference sequences available in GenBank. Genetic diversity was assessed using DnaSP v6.12.03, while phylogenetic reconstruction was performed using MEGA 11 based on the Neighbor-Joining (NJ) method with the Kimura 2-Parameter model. The results showed that the nucleotide composition consisted of Adenine (A) 29.3%, Thymine (T) 19.8%, Cytosine (C) 26.9%, and Guanine (G) 24.1%, with a G+C content (51.0%) slightly higher than the A+T content (49.0%). Genetic diversity analysis revealed a haplotype diversity value of 0.533 ± 0.172 and a nucleotide diversity value of 0.00145 ± 0.00047. Phylogenetic reconstruction produced a consistent tree topology across two outgroup models, with all M. cumingii samples forming a single clade supported by high bootstrap values (99–100%). The phylogenetic relationships among M. cumingii samples from Kabetan Island, Tolitoli, were very close, as indicated by genetic distance values ranging from 0.000 to 0.003.